Characterization of the KTH high-flux solar simulator combining three measurement methods. (15th December 2017) - Garrido, Jorge; Aichmayer, Lukas; Wang, Wujun; Laumert, Björn
Abstract: This paper presents the characterization of the first Fresnel lens-based High-Flux Solar Simulator (HFSS) showing the evaluation of the total thermal radiative power dependent on the aperture radius at the focal plane. This result can be directly applied to calculate the thermal power input into any solar receiver tested in the KTH HFSS. Three measurement setups were implemented and their results combined to assess and verify the characterization of the solar simulator: a thermopile sensor measuring radiative flux, a CMOS camera coupled with a Lambertian target to obtain flux maps, and a calorimeter to measure the total thermal power within an area of 300×300 mm. Finally, a Monte Carlo analysis was performed to calculate the total uncertainties associated to each setup and to combine them to obtain the simulator characterization. The final result shows a peak flux of 6.8 ± 0.35 MW/m 2 with a thermal power of 14.7 ± 0.75 kW within an aperture of 180 mm in diameter at the focal plane, and a thermal-electrical conversion efficiency of 25.8 ± 0.3%. It was found very good repeatability and a stable energy output from the lamps during the experiments. Highlights: Final characterization of the first Fresnel lens-based solar simulator. Comparison, suitability assessment and combination of three measurement methods. Detailed uncertainty analysis increasing confidence level with a Monte-Carlo method. The total lab performance is compared to each individual lamp contribution.